Amino acid toxicity in Zebrafish - Vieira, Pedro Emanuel Ferreira dos Reis (2013)
Proteins are synthetized through the mechanism of translation and are constituted by amino acids. Besides being the basic units of proteins, amino acids also play other important roles in the cell such as signaling or regulation of cell growth. However, in excess, amino acids can be toxic, although the mechanism of toxicity is still not clear. In this study we used zebrafish as a vertebrate model to assess the toxicity induced by different amino acids as a result of nutritional imbalance. Moreover, we evaluated the changes induced by amino acid toxicity during zebrafish development in order to understand if this toxicity could be related with wrong incorporation of mischarged amino acids during translation. The results show that some of the canonical amino acids cause high toxicity in zebrafish, namely L-tryptophan, L-glutamine, Lphenylalanine and L-arginine. To understand if this toxicity could be caused by the production of aberrant proteins, due to tRNA mischarging, result of an unbalanced amino acid pool, we analyzed the activation of protein degradation pathways. For this we did western blot analysis of the poliubiquitination state of the proteome. No differences were observed between different amino acid concentrations and the control indicating that the ubiquitin-proteasome pathway is not directly correlated with the amino acid toxicity observed.